Does Bi-exponential Fitting Perform better than Mono-exponential Fitting in IVIM-DWI? An Assessment of Renal Pathological Injury of IgA Nephropathy - Mao, Wei; Ding, Xiaoqiang; Ding, Yuqin; Fu, Caixia; Zeng, Mengsu; Zhou, Jianjun (Current Medical Imaging, 2024)
Background Chronic kidney disease has become one of the world's major public health problems, immunoglobulin A (IgA) nephropathy is a common pathological type of CKD. Delaying the progression of IgA nephropathy has currently become the main clinical treatment strategy, precise evaluation of renal pathological injury during follow-up of patients with IgA nephropathy is important. Therefore, it is imperative to develop an accurate and non-invasive imaging technique for effective follow-up of renal pathological injury in patients with IgA nephropathy. Objective To investigate the clinical value of intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) in assessing renal pathological injury in patients with immunoglobulin A (IgA) nephropathy compared with a mono-exponential model. Methods Altogether, 80 patients with IgA nephropathy were divided into the mild (41 cases) andmoderate–severe (m–s) renal injury groups (39 cases) according to pathology scores, and 20 healthy volunteers were recruited as controls. All participants underwent IVIM-DWI of the kidneys, and renal parenchymal apparent diffusion coefficient (ADC), pure molecular diffusion coefficient (D), pseudo-diffusion coefficient (D*), and perfusion fraction (f) values were measured. One-way analysis of variance, receiver operating characteristic (ROC) curve analysis, and Pearson correlation analysis were performed for all the DWI-derived parameters. Results The DWI-derived parameters of the m–s renal injury group were significantly lower than those of the mild renal injury and control groups (P < 0.01). The ROC analysis revealed that f had the largest area under the ROC curve for differentiation between the m–s and mild renal injury groups and between the m–s renal injury and control groups. The f had the largest correlation coefficient with renal pathology scores (r=−0.81), followed by the D* (−0.69), ADC (−0.54), and D values (−0.53), respectively (all P<0.01). Conclusion IVIM-DWI demonstrated better diagnostic performance than the mono-exponential model in assessing renal pathological injury in patients with IgA nephropathy.
Keywords: Intravoxel incoherent motion